2017
DOI: 10.3390/ijerph14050514
|View full text |Cite
|
Sign up to set email alerts
|

Two Single Nucleotide Polymorphisms (rs2431697 and rs2910164) of miR-146a Are Associated with Risk of Coronary Artery Disease

Abstract: The coronary artery disease (CAD) is one of the most severe cardiovascular diseases. MicroRNA-146a (miR-146a) influences the pathology of cardiovascular diseases. Two single nucleotide polymorphisms (SNPs) of miR-146a (rs2431697 and rs2910164) have been reported to alter the function or expression of microRNA. The purpose of this study is to evaluate the association between miR-146a gene polymorphism and the risk of CAD in the Chinese population. A total of 353 CAD patients and 368 controls were recruited, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 22 publications
2
18
1
Order By: Relevance
“…Through decades of investigations, thousands of miRNAs have been found in humans and animals, among which a notable proportion of miRNAs are found to be critical in the pathogenesis of various diseases, including cardiovascular diseases [9,10,11,12,13,14]. Moreover, some circulating miRNAs predominantly express in CAD patients [15,16]. miR-126 is one of the miRNAs that is abundantly expressed in endothelial cells, regulating inflammatory responses and endothelial cellular activities [17,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Through decades of investigations, thousands of miRNAs have been found in humans and animals, among which a notable proportion of miRNAs are found to be critical in the pathogenesis of various diseases, including cardiovascular diseases [9,10,11,12,13,14]. Moreover, some circulating miRNAs predominantly express in CAD patients [15,16]. miR-126 is one of the miRNAs that is abundantly expressed in endothelial cells, regulating inflammatory responses and endothelial cellular activities [17,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that SNPs in miR-146 may increase the susceptibility of cardiovascular disorders, including coronary artery disease. For instance, in a study by Wang et al , a total of 353 Chinese patients with coronary artery diseases and 368 controls were evaluated 21. According to this study, (C allele) of rs2910164 was more frequent in the patients.…”
Section: Discussionmentioning
confidence: 91%
“…One article was excluded because the study cohort included patients with peripheral artery atherosclerosis as well as patients with CCDs, and authors did not report the genotype counts of CCD patients separately [3]. Finally, a total of 51 eligible articles remained [4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54]. A total of 31 miRNA polymorphisms were evaluated in these articles (Table 1 and Table S1).…”
Section: Resultsmentioning
confidence: 99%